INSTITUTE OF RENEWABLE ENERGY OF THE NAS OF UKRAINE – 20 YEARS - Kudrya, S.; Kuznietsov, M.; Yatsenko, L. (Institute of Renewable Energy National Academy of Sciences of Ukraine, 2023)
Today, the use of renewable energy sources (RES) is one of the main priorities of energy development for most of the developed countries of the world. In particular, the USA, Germany, Spain, Sweden, Denmark, and Japan plan to increase the share of RES in the total energy balance to 50% in the first half of the 21st century, but the number of countries, cities and individual communities that aim to ensure energy consumption through RES is steadily increasing, and some of them aim to switch to RES at the level of 100%. The energy strategy of Ukraine foresees that by 2035 the share of RES in Ukraine will be 25%. But in view of the destruction caused by the enemy to thermal generation facilities and power supply networks of Ukraine, the state must strengthen the development of RES and accelerate the energy transition: this is a matter of national security and security of electricity transmission, for the solution of which Ukraine must fully use its scientific and technical potential , in which the main role is given to scientific institutions that deal with the development of renewable energy systems. The flagship among such scientific institutions is definitely the Institute of Renewable Energy of the National Academy of Sciences of Ukraine, which has absorbed the experience and knowledge of several generations of RES scientists and created a unique research and experimental base for realizing their potential. The article presents factual materials regarding the areas of activity, scientific potential, achievements, as well as the history and prerequisites for the establishment of the Institute of Renewable Energy of the National Academy of Sciences of Ukraine. This information is about the management of the Institute, its structure by departments and their tasks.